2021
DOI: 10.1177/23259671211048248
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lower Extremity Injury Risk Associated With Player Load and Distance in Collegiate Women’s Soccer

Abstract: Background: There is limited research regarding the impact of workload on injury risk specific to women’s soccer. Wearable global positioning system (GPS) units can track workload metrics such as total distance traveled and player load during games and training sessions. These metrics can be useful in predicting injury risk. Purpose: To examine the relationship between injury risk and player workload as collected from wearable GPS units in National Collegiate Athletic Association (NCAA) Division I women’s socc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…It is important to note that, despite ACWR derived from s-RPE not being a good predictor of injury [ 42 ], our outcomes observed across the in-season period did not reach the suggested “danger zone” (ACWR ≥ 1.5) [ 43 ]. This result is in line with another study performed with 65 players from Division I in the United States, which reported this ratio was not associated with injury [ 44 ], although some studies reported associations between ACWR and non-contact injury occurrences [ 42 , 45 , 46 , 47 , 48 ]. In fact, ACWR score has also been related to perceived effort in women athletes [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…It is important to note that, despite ACWR derived from s-RPE not being a good predictor of injury [ 42 ], our outcomes observed across the in-season period did not reach the suggested “danger zone” (ACWR ≥ 1.5) [ 43 ]. This result is in line with another study performed with 65 players from Division I in the United States, which reported this ratio was not associated with injury [ 44 ], although some studies reported associations between ACWR and non-contact injury occurrences [ 42 , 45 , 46 , 47 , 48 ]. In fact, ACWR score has also been related to perceived effort in women athletes [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…European reports did not acknowledge the potential complicating factor of the effects of increases in the acute-to-chronic workload ratio (ACWR). Periods of inactivity followed by higher demand activity increases the ACWR and the subsequent risk of injury, founded in several sports [ 25 ], including football [ 26 , 27 ], according to data presented in this pilot study with professional football players.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 47 It has been shown that 18.3% of current collegiate and professional women’s soccer players have a history of at least 1 ACL injury. 50 Risk factors associated with ACL injury in female athletes include neuromuscular imbalances, 21 hormonal fluctuations, 11 , 20 narrower intercondylar notch width, 39 , 40 , 42 joint laxity, 32 , 43 workload, 51 and landing mechanics. 24 , 33 Our investigation demonstrated that playing soccer games on AT may be an additional risk factor for ACL injury specifically for female athletes.…”
Section: Discussionmentioning
confidence: 99%